Women From Different Ethnic Groups and Their Experiences With Victimization and Seeking Help. (March 2015) - Postmus, Judy L.
For women who experience abuse in childhood or adulthood, the assumptions are that surviving includes seeking help. This article presents an exploratory study on the prevalence of victimization in the lives of Caucasian, African American, and Latina women, if and to whom they disclosed their victimization, and where they turned for services and support. The results indicate Caucasian women turn more to traditional, therapeutic sources compared with African American women, who tend to use tangible supports. However, when controlling for a number of key variables, the ethnic differences disappear. Implications for further research and practice conclude this article.